EFFECTIVE APPLICATION OF SCANNING ELECTRON MICROSCOPY IN FORENSIC BIOLOGY FOR THE ANALYSIS OF HAIRS FROM EXTINCT AND EXTANT MAMMALIAN SPECIES - Ol'ga F. Chernova; Tat'yana V. Perfilova (Теория и практика судебной экспертизы)
The possibilities of scanning electron microscopy (SEM) for effective species diagnosis and identification of mammals are demonstrated using specific examples of microscopic analysis of mammalian fur, including the fur of extinct species of the Ice Age (woolly mammoth, woolly rhinoceros, cave lion, ancient bison and horses), fur remains from Holocene burials and graves, and fur samples from extant threatened species (chimpanzee, orangutan, Amur leopard, and tiger).